2017
DOI: 10.1111/nyas.13419
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing a mouse model for evaluation of countermeasures against hydrogen sulfide–induced neurotoxicity and neurological sequelae

Abstract: Hydrogen sulfide (H S) is a highly neurotoxic gas. It is the second most common cause of gas-induced deaths. Beyond mortality, surviving victims of acute exposure may suffer long-term neurological sequelae. There is a need to develop countermeasures against H S poisoning. However, no translational animal model of H S-induced neurological sequelae exists. Here, we describe a novel mouse model of H S-induced neurotoxicity for translational research. In paradigm I, C57/BL6 mice were exposed to 765 ppm H S for 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(97 citation statements)
references
References 56 publications
11
86
0
Order By: Relevance
“…Previous work in our laboratory found that H 2 S inhibits cytochrome c oxidase in multiple brain regions . We investigated cytochrome c oxidase activity in H 2 S‐poisoned mice treated with saline versus those treated with Cob.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work in our laboratory found that H 2 S inhibits cytochrome c oxidase in multiple brain regions . We investigated cytochrome c oxidase activity in H 2 S‐poisoned mice treated with saline versus those treated with Cob.…”
Section: Resultsmentioning
confidence: 99%
“…All animal studies were approved by the Iowa State University Institutional Animal Care and Use Committee. Only male mice were used in this study because previous studies showed that male are more sensitive to H 2 S‐induced neurotoxicity than female mice . The 7‐ to 8‐week‐old C57/BL6 male mice were purchased from the Jackson Laboratories (Bar Harbor, ME), and weighed 20–25 g at the beginning of the experiment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations